Evaluation of simple cost-effective immuno-haematological markers to predict outcome in hospitalized COVID-19 patients during second wave - Manaswini Yadav, Golla Anmol; Venkateshwarlu, Chegowni; Reddy, Varsha; Raghuveer, P.; Manjula, B. S. V. (International Journal of Advances in Medicine, 2022)
Background: COVID-19 pandemic has strained the health infrastructure globally, hence the importance of cost-effective biomarkers. We aimed to identify simple haematological prognostic markers in hospitalized COVID-19 patients to differentiate between milder and severe cases, thus predicting outcome. Methods: A retrospective study of COVID-19 patients admitted at Malla Reddy institute of medical sciences was conducted from April to June 2021. Total leukocyte count (TLC), neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR) and platelet-to-lymphocyte ratio (PLR) were calculated and correlated with outcome. These parameters were compared with other inflammatory markers using ROC (receiver operator curve) analysis. Results: 303 patients of 397 fulfilled the inclusion criteria (male-198, female-105). There was a significant higher mean of NLR in patients with death (14.46±5.84) compared to patients recovered (8.43±4.33), similarly the dNLR was higher in death (8.06±2.34) compared to recovered (4.97±1.49). A significant positive strength of association between the NLR and dNLR with the ESR, CRP, CORADS score and CT severity score in the patients. The ROC analysis showed the NLR (AUC=0.777) and dNLR (0.799) a better marker to predict the outcome. Conclusions: In COVID-19, immuno-haematological markers like NLR, dNLR, PLR found to be a simple and cost-effective tool to prognosticate the clinical outcome among hospitalized patients and were in concordance with the other inflammatory markers. Hence, these markers serve as better indicators in risk stratification and better management.